Extreme Weather and Melioidosis : An endemic tropical disease in Penampang district of Sabah, Malaysia - Sam Froze, Jiee; Lim, Kai Joo; Daryl Sin, Choon Vui; Dina, Peter Marius; NurulI IllSyafiqah, Ilyana; Anisah, Jantim (College of Public Health Sciences, Chulalongkorn University, 2023)
Background: Melioidosis is a fatal, but preventable communicable disease that is endemic in several parts of the world, including the state of Sabah, Malaysia, which is located in the northern part of Borneo Island. Flooding is one of the most regular natural disasters affecting some parts of Malaysia, including Sabah. The main aim of this study was to determine if rainfall and floods were significant risk factors contributing to the substantial burden of melioidosis in the Penampang district from 2015 to 2020. Method: We analyzed 64 culture-confirmed cases of melioidosis in the Penampang district, Sabah, between 2015 and 2020 to determine if rainfall and floods were significant risk factors that contributed to the substantial burden of melioidosis. Fisher's exact test was used to examine for associations between risk factors and melioidosis mortality. We used Poisson regression to calculate the incidence rate ratio for melioidosis cases based on different risk factors. Results: There was a linear association between rainfall and floods with cases of melioidosis. Our Poisson regression results indicated that the number of melioidosis cases was 1.002 times greater with every 1 mm increase of rainfall and 2.203 times greater with every flood event. There was a linear association between cases of melioidosis with rainfall and floods, with most patients having comorbidities. Conclusion: Prevention of melioidosis in the Penampang district should primarily focus on avoiding direct contact with soil or contaminated water, especially during or after extreme weather events. Continuous and community-empowered health education targeting the high-risk group is essential, as flash floods in certain parts of the state and districts are seasonal and unpredictable.